The Biml book : business intelligence and data warehouse automation /: business intelligence and data warehouse automation. ([2017]) - Leonard, Andy; Currie, Scott; Alley, Jacob; Andersson, Martin; Avenant, Peter; Fellows, Bill; Peck, Simon; Smith, Reeves; Sondak, Raymond; Weissman, Benjamin
No abstract available